The Influence Of Advertising Attraction, Price And Timeliness On Interest Users Of Online Grab Transportation Services In Bengkulu City - Asandy Azwar Tanjung; Subandrio Subandrio (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2023)
The title of this research is the Effect of Advertising Attractiveness, Price and Timeliness on the Interests of Grab Online Transportation Service Users in Bengkulu City. This study aims to determine the effect of advertising attractiveness, price and timeliness on the interest of users of Grab Online Transportation Services in Bengkulu City. The study was conducted from January 2023 until completion.The sample of this research is consumers of Grab Online Transportation Service Users in Bengkulu City, totaling 75 people. The sampling technique is probability sampling. The method used in this study is a quantitative method with Multiple Linear Regression analysis using SPSS 24 for windows.Based on the results of multiple linear regression, the following equation is obtained: Y = 1.310 + 0.403 (X1) + 0.458 (X2) + 0.720 (X3). The research results and hypotheses in this study indicate that advertising attractiveness (X1) price (X2) and accuracy Time (X3) has a positive and significant effect both partially and simultaneously on Service User Interest (Y) in Bengkulu City Grab Online Transportation.